2008
DOI: 10.1007/s10029-008-0380-2
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic repair of parahiatal hernias with mesh: a retrospective study

Abstract: Primary parahiatal hernias occur as a result of a congenital weakness and secondary defects follow hiatal surgery. The use of a mesh is advisable for large defects and defects of primary type. Secondary hernias following fundoplication do not need a redo fundoplication, but require an adequate crural repair with mesh. Laparoscopic repair of these uncommon hernias is safe, effective and provides all of the benefits of minimally invasive surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(49 citation statements)
references
References 12 publications
1
48
0
Order By: Relevance
“…(11)(12)(13)(14)(15)(16)(17) All the cases reported, including those of the present study, were left parahiatal hernias, suggesting that left parahiatal hernias are more common than right parahiatal hernias. Therefore, it is important to pay attention when dissecting in the region to the left of the diaphragmatic crura during surgery to treat an apparent PEH, so that the possibility of a parahiatal hernia can be excluded.…”
Section: Discussionsupporting
confidence: 46%
See 2 more Smart Citations
“…(11)(12)(13)(14)(15)(16)(17) All the cases reported, including those of the present study, were left parahiatal hernias, suggesting that left parahiatal hernias are more common than right parahiatal hernias. Therefore, it is important to pay attention when dissecting in the region to the left of the diaphragmatic crura during surgery to treat an apparent PEH, so that the possibility of a parahiatal hernia can be excluded.…”
Section: Discussionsupporting
confidence: 46%
“…(11) Similarly, Palanivelu et al reported a low incidence of parahiatal hernia (0.35%, 4/1,127) in their cohort of HH patients who were laparoscopically treated in a single Asian centre. (13) The unusually high proportion of parahiatal hernias in our hospital (20%, 2/10) might either indicate an underreporting of HHs (thereby leading to the smaller overall number of HHs being treated), or suggest that parahiatal hernia is an underappreciated condition that should be actively excluded in the differential diagnosis during surgical exploration of all PEHs.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…To reduce the incidence of recurrence, laparoscopic surgeons have begun to buttress most paraesophageal hernia repairs with prosthetic material [6,7]. A group from Israel reported on 59 patients who had either recurrent or large paraesophageal hernias repaired laparoscopically with mesh reinforcement.…”
Section: Introductionmentioning
confidence: 99%
“…During a mean follow-up period of 28 months, six patients (13%) experienced a recurrent hernia [6]. Palanivelu et al [7] reported on 21 cases of adult diaphragmatic hernias repaired laparoscopically, with mesh used in 18 patients (86%). After the use of minimally invasive techniques, recurrence was experienced by only one patient (5%).…”
Section: Introductionmentioning
confidence: 99%